INFORMATION ABOUT AUTHORS - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2013)
VANDA ARAMAVIČIŪTĖ – Habilitated Doctor of Social Sciences (Education), Professor at the Department of Education, Vilnius University; Research interests: general educology, education and spiritual development of personality, methodology of educational research; Address: 9/1 Universiteto Str., LT-O1513 Vilnius, Lithuania; E-mail address: aramaviciute@gmail.com TATJANA BULAJEVA – Doctor of Social Sciences (Education), Associate Professor at the Department of Education, Vilnius University; Research interests: education policy and management with the current focus on teacher education policy, language education policy; Address: 9/1 Universiteto Str., LT-O1513 Vilnius, Lithuania; E-mail address: ttjnbulajeva@gmail.com DAIVA BUBELIENĖ – Doctor of Social Sciences; Šiauliai University, Faculty of Education, Department of Education Research interests: human resource management, quality of life, social research methodology Address: 25 P. Višinskio Str., Šiauliai, Lithuania; E-mail address: daivabubeliene@gmail.com DAIVA JUOZAPAVIČIENĖ – Psychologist of the Valakupiai Rehabilitation Center Address: 69 Vaidilutės Str., LT-10100 Vilnius; Lithuania; E-mail address: daiva.juozapaviciene@reabilitacija.lt ANTANAS KAIRYS – Doctor of Social Sciences (Psychology), Lecturer at the Department of General Psychology, Vilnius University; Research interests: time psychology, career psychology, personality traits; Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; E-mail address: antanas.kairys@fsf.vu.lt DAIVA GRAKAUSKAITĖ KARKOCKIE- NĖ – Doctor of Social Science (Psychology); Associate Professor at the Department of Psychology of Didactics, Lithuanian University of Educational Sciences; Research interests: psychology of creativity, gifted children, family psychology. Address: 39-328 Studentų Str., LT-08106 Vilnius, Lithuania; E-mail address: daiva.karkockiene@leu.lt MARGARITA KOZHEVNIKOVA – PhD, Senior Researcher at Institute of Teacher and Adult Education, Russian Academy of Education, St. Petersburg, Russia; Research interests: philosophy of education in the Buddhist tradition; teacher’s self-awareness as a philosophical problem; a model of education as bringing to the personal maturity; language of pedagogy; phenomenological aspects of researching the methodology of pedagogic educational research methodology; ethnic and religious problems in education; E-mail address: margaritakozh@ya.ru AUDRONĖ LINIAUSKAITĖ – Doctor of Social Sciences (Psychology), Professor at the Department of Psychology, Klaipėda University; Research interests: psychological time, career psychology, psychological well-being; Address: 5 S. Nėries Str., LT-92227 Klaipėda, Lithuania; E-mail address: audrone.liniauskaite@gmail.com GEDIMINAS MERKYS – Habilitated Doctor of Social Sciences, Professor, Head of the Social Research Laboratory, Kaunas University of Technology; Research interests: social research methodology (quantitative and qualitative), diagnostics in psychology, management diagnostics, social indicators, sociology of organizations; Address: 20 K. Donelaičio Str., Kaunas, Lithuania; E-mail address: gediminas.merkys@ktu.lt BIRUTĖ POCIŪTĖ – Doctor of Social Sciences (Psychology), Associate Professor at the Department of General Psychology, Vilnius University; Research interests: educational psychology, psychology of career choice, learning; Address: 9/1 Universiteto Str., LT-O1513 Vilnius, Lithuania; E-mail address: birute.pociute@fsf.vu.lt RASA RUDŽINSKIENĖ – PhD student of Faculty of Education, Šiauliai University; Director of employment agency “Jurgvita”; Research interests: planning of career, professional counselling, coaching; Address: 25 P.Višinskio Str., LT-76351 Šiauliai, Lithuania; E-mail address: karjerosprojektavimas@gmail.com VADIM ROUK – PhD candidate, Tallinn University; Researcher at the Institute of Educational Sciences, Tallinn University; Research interests: curriculum history and theory; curriculum development; political history of Estonia; history of France, Great Britain and South Arfica; holistlic philosophy; Address: Tallinn University, Rüütli 6, 10130, Tallinn, Estonia; E-mail address: vadim.rouk@tlu.ee AUŠRA RUTKIENĖ – PhD, Associate Professor at the Department of Education, Vytautas Magnus University; Research interests: methodology of social research, qanititative research, statistical data analysis, adult learning; Address: 52-301K. Donelaičio Str., LT-44244 Kaunas, Lithuania; E-mail address: a.rutkiene@smf.vdu.lt RŪTA SARGAUTYTĖ – Doctor of Social Sciences (Psychology), Associate Professor at the Department of Clinical and Organizational Psychology; Research interests: vocational rehabilitation, cross-cultural psychology, medical psychology, patient education; Address: 9/1 Universiteto Str., LT-O1513 Vilnius, Lithuania; E-mail address: ruta.sargautyte@fsf.vu.lt EDITA ŠATIENĖ – Directress of the Valakupiai Rehabilitation Center; Address: Vaidilutės Str., 69, LT-10100 Vilnius; Lithuania; E-mail address: edita.satiene@reabilitacija.lt. El. paštas: i.tandzegolskienė@smf.vdu.lt ILONA TANDZEGOLSKIENĖ – PhD, Lecturer at the Department of Education, Vytautas Magnus University; Research interests: expression of Students’ independent activities, preparation of career specialists, career and labour marker, career in different stages of human development, possibilities for employability, levels in the qualification frameworks, preparation of description of qualifications, objectives of scientific activity; Address: 52-301 K. Donelaičio Str., LT-44244 Kaunas, Lithuania; E-mail address: i.tandzegolskienė@smf.vdu.lt VILIJA TARGAMADZĖ – Habilitated Doctor of Social Sciences (education), Professor at the Department of Education, Vilnius University; Research interests: social education; education management; problem-based learning; Address: 9/1 Universiteto Str., LT-O1513 Vilnius, Lithuania; E-mail address: vilija.targamadze@gmail.com ONA TIJŪNELIENĖ – Habilitated Doctor of Social Sciences (education), Professor at the Department of Education, Klaipeda University; Research interests: philosophy of education, methodology of educational research, history of educology; Address: 5 S. Nėries Str., LT-92227 Klaipėda, Lithuania; E-mail address: onatij@one.lt IEVA URBANAVIČIŪTĖ – PhD, Lecturer at the Department of Psychology Didactics, Lithuanian University of Educational Sciences; Research interests: career psychology, work psychology, learning and work motivation; Address: 39 Studentų Str., LT-08106 Vilnius, Lithuania; E-mail address: ieva.urbanaviciute@gmail.com